2019
DOI: 10.7196/samj.2019.v109i7.14127
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of and risk factors for gestational diabetes mellitus in South Africa

Abstract: Gestational diabetes mellitus (GDM), defined as glucose intolerance with onset or first recognition during pregnancy, [1] is one of the leading causes of morbidity and mortality for mothers and infants worldwide. Globally, ~16.2% (21.3 million) of live births are associated with hyperglycaemia in pregnancy, of which 86.4% are due to GDM, 6.2% to pre-existing type 1 diabetes (T1D) or type 2 diabetes (T2D), and 7.4% to T1D and T2D first detected during pregnancy. [2] The prevalence of GDM is rapidly increasing w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 32 publications
0
10
0
Order By: Relevance
“…A study conducted in a population of urban Black African women in Gauteng reported an IGT prevalence of 20.3% [ 51 ], identifying these women as a high-risk group that requires monitoring and intervention to prevent the development of T2DM. Furthermore, these women are of reproductive age and at risk for developing gestational diabetes, which poses an intergenerational risk of obesity and T2DM to their children [ 52 ].…”
Section: Discussionmentioning
confidence: 99%
“…A study conducted in a population of urban Black African women in Gauteng reported an IGT prevalence of 20.3% [ 51 ], identifying these women as a high-risk group that requires monitoring and intervention to prevent the development of T2DM. Furthermore, these women are of reproductive age and at risk for developing gestational diabetes, which poses an intergenerational risk of obesity and T2DM to their children [ 52 ].…”
Section: Discussionmentioning
confidence: 99%
“…It has been estimated that insulin sensitivity is decreased by up to 40% in pregnant women with GDM compared to women with normoglycemia [21,28]. Although GDM is reported to affect ≈14% of pregnancies globally, rates between 1% and 28% are reported in different regions, varying according to ethnicity, geographical location (urban vs. rural), environmental factors, and the screening and diagnostic strategies employed [29]. GDM imposes significant economic costs on health systems.…”
Section: Gestational Diabetes Mellitusmentioning
confidence: 99%
“…The prevalence of GDM has steadily increased over the last 20 years, paralleling the rising obesity epidemic. Globally, it is estimated that 14% of pregnancies are affected by GDM [ 70 ], although rates vary between 1–28% depending on the population studied and the diagnostic criteria used [ 71 ]. The economic costs of GDM are high [ 72 ] and it has been estimated that the health care costs of treating women with GDM are ~25.1% higher than treating women without GDM [ 73 ].…”
Section: Adiponectin In Common Pregnancy Disordersmentioning
confidence: 99%
“…Early detection and treatment may reduce adverse pregnancy outcomes including stillbirth, neonatal macrosomia, neonatal hypoglycaemia, birth trauma and neonatal respiratory distress syndrome as well as decrease the risk of preeclampsia in the mother. The common risk factors, which include overweight or obesity, excessive gestational weight gain, advanced maternal age, family history of diabetes, previous history of GDM and adverse pregnancy outcomes, however, have poor predictive value and fail to identify a large percentage of women at risk for GDM, thus limiting their use as screening tools [ 71 , 80 , 81 ]. Currently the gold-standard for the diagnosis of GDM is the oral glucose tolerance test (OGTT) performed at 24–28 weeks gestation, although technical challenges, which include the requirement for fasting and multiple blood draws, and the high costs associated with sending blood samples to reference laboratories for testing, limit its widespread use [ 13 ].…”
Section: Adiponectin In Common Pregnancy Disordersmentioning
confidence: 99%